Cellular manufacturing systems design, planning and control - Singh, Nanua (Chapman & Hall, 1996)
The focus of this book is the modeling and analysis of cellular manufacturing systems. Cellular manufacturing, an application of Group Technology, has contributed significantly to revolutionizing the management of modern low volume/high variety manufacturing systems.